1988
DOI: 10.1007/bf00391499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fosfomycin, mesna, and sodium thiosulfate on the toxicity and antitumor activity of cisplatin

Abstract: Fosfomycin and mesna were investigated in rats and mice concerning their detoxifying effects on cisplatin toxicity in comparison to sodium thiosulfate, a known protector against cisplatin nephrotoxicity. After separate i.p. injection of cisplatin and fosfomycin (500 mg/kg) or mesna (800 mg/kg) a slight increase in the 50% lethal dose of cisplatin was found in all animals. In mice sodium thiosulfate proved to be far more effective in preventing lethal toxicity and nephrotoxicity as measured by blood urea nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Fosfomycin is reported to possess a wide variety of biological activities other than bacterial growth inhibition or bactericidal action. These include an effect on hu-man T-lymphocyte function (20), an effect on cytokine production by human monocytes (21), and an effect that reduces the toxicity caused by cisplatin (30). Some of these activities are also shown by the enantiomer of fosfomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Fosfomycin is reported to possess a wide variety of biological activities other than bacterial growth inhibition or bactericidal action. These include an effect on hu-man T-lymphocyte function (20), an effect on cytokine production by human monocytes (21), and an effect that reduces the toxicity caused by cisplatin (30). Some of these activities are also shown by the enantiomer of fosfomycin.…”
Section: Discussionmentioning
confidence: 99%
“…First signs of structural regeneration were observed 7 days after cisplatin injection [ 10 , 111 ]. However, in case of lethal dose death may occur within 10 days [ 112 ].…”
Section: The Heterogeneity Of Cisplatin Protocolsmentioning
confidence: 99%
“…It has been reported that fosfomycin did not influ ence the tumoricidal action of cisplatinum in the treatment of Ll210 leukemia in mice, although it did r educe the tumoricidal efficacy of cispla tinum against Yoshida ascites sarcoma in rats. 14 We have previously shown that fosfomycin did not interfere with ci s-platinum's tumoricidal actions against SCCA cell Jines in an in vitro system. 1 5 Using a nude mouse model, this experiment was design ed to further evaluate the interaction between fosfomycin and cis-platinum regarding the tumoricidal actions of cis-platinum.…”
Section: Introductionmentioning
confidence: 99%